2014
DOI: 10.1007/s10461-014-0858-0
|View full text |Cite
|
Sign up to set email alerts
|

HIV Prevalence and Risk Behaviors Among Female Sex Workers in Botswana: Results from the 2012 HIV/STI Bio-Behavioral Study

Abstract: To evaluate HIV/STI prevalence among female sex workers (FSWs) in Botswana, and assess HIV-related risk behaviors. Cross-sectional study using time-location sampling in three districts of Botswana. Adjusted HIV prevalence at district level ranged from 53.5 to 68.5 %. Syphilis prevalence ranged from 3.7 to 14.5 %; chlamydia prevalence ranged from 4.8 to 16.3 %; and gonorrhoea prevalence ranged from 8.3 to 11.7 %. FSWs had been practicing sex work for a mean of 4.7 years, and had a mean of 7.6 sex partners in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
17
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 10 publications
(12 reference statements)
0
17
1
Order By: Relevance
“… 32 33 Also, as is indicated by our findings, age and duration of sex work were not significantly associated with recent syphilitic infection. The prevalence of prevalent syphilis reported in our study is much higher than that reported among FSWs in other developing countries, for example, 4–15% in Botswana, 34 and 2–9% in Sudan. 35 The low HIV prevalence may be due to relatively short duration of sex work as the study participants entered sex work only in their mid-30s and had been in sex work for a time period ranging from 1 to 6 years.…”
Section: Discussioncontrasting
confidence: 80%
See 1 more Smart Citation
“… 32 33 Also, as is indicated by our findings, age and duration of sex work were not significantly associated with recent syphilitic infection. The prevalence of prevalent syphilis reported in our study is much higher than that reported among FSWs in other developing countries, for example, 4–15% in Botswana, 34 and 2–9% in Sudan. 35 The low HIV prevalence may be due to relatively short duration of sex work as the study participants entered sex work only in their mid-30s and had been in sex work for a time period ranging from 1 to 6 years.…”
Section: Discussioncontrasting
confidence: 80%
“…The prevalence is even higher than it is in the most economically-devastated countries (eg, Botswana and Sudan). 34 35 As the epidemics of STIs spread among both middle-aged FSWs and younger FSWs, intervention priority should be placed on both groups. Combined intervention programmes that integrate both behavioural component (promotion of condom use) and biomedical component (treatment of STIs) need to be developed and evaluated among middle-aged FSWs as well as their clients.…”
Section: Discussionmentioning
confidence: 99%
“…Heterosexual transmission is the main mode of HIV transmission in sub-Saharan Africa, and sex work is a driver of the epidemic. [1][2][3][4] Female sex workers (FSW) in sub-Saharan Africa have a very high burden of HIV, [5] with HIV prevalence estimated to be at least three times that of general population [6][7][8][9][10]. Recent years have seen increased research in this key population in various sub-Saharan African countries.…”
Section: Introductionmentioning
confidence: 99%
“…Only two published studies have focused on FSW in Botswana. [7,28] One of the studies showed that, although most FSW had been tested for HIV at least once (and had HIV prevalence of 60%), regular HIV testing was infrequent. [7] The other study was conducted amongst 17 FSW in a mine town in Botswana: two focus groups and five in-depth interviews were conducted, and participants expressed negative attitudes towards HIV self-testing due to lack of knowledge and confidence to perform the testing independently.…”
Section: Introductionmentioning
confidence: 99%
“…[24][25][26] Ultimately, relationship dynamics and the other perceived benefits of PrEPthose beyond HIV prevention-must be taken into consideration when providing HIV risk-reduction counseling for individuals using PrEP. This approach will allow programs to provide better support of PrEP users' overall sexual health and well-being.…”
Section: Discussionmentioning
confidence: 99%